2021
DOI: 10.7554/elife.65304
|View full text |Cite
|
Sign up to set email alerts
|

The corticospinal tract primarily modulates sensory inputs in the mouse lumbar cord

Abstract: It is generally assumed that the main function of the corticospinal tract (CST) is to convey motor commands to bulbar or spinal motoneurons. Yet the CST has also been shown to modulate sensory signals at their entry point in the spinal cord through primary afferent depolarization (PAD). By sequentially investigating different routes of corticofugal pathways through electrophysiological recordings and an intersectional viral strategy, we here demonstrate that motor and sensory modulation commands in mice belong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 84 publications
(161 reference statements)
1
20
1
1
Order By: Relevance
“…The brainstem, however, has recently emerged as a critical motor control center that is also responsible for skilled limb movements (Esposito et al, 2014;Ruder et al, 2021), and receives significant cortical projections (Economo et al, 2016(Economo et al, , 2018. In this regard, recent work has further identified that cortico-brainstem projections provide specific modulatory roles required for dexterous movement that are distinct from corticospinal projections (Conner et al, 2021;Moreno-Lopez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The brainstem, however, has recently emerged as a critical motor control center that is also responsible for skilled limb movements (Esposito et al, 2014;Ruder et al, 2021), and receives significant cortical projections (Economo et al, 2016(Economo et al, , 2018. In this regard, recent work has further identified that cortico-brainstem projections provide specific modulatory roles required for dexterous movement that are distinct from corticospinal projections (Conner et al, 2021;Moreno-Lopez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The brainstem, however, has recently emerged as a critical motor control center that is also responsible for skilled limb movements (Esposito et al, 2014; Ruder et al, 2021), and receives significant cortical projections (Economo et al, 2016, 2018). In this regard, recent work has further identified that cortico-brainstem projections provide specific modulatory roles required for dexterous movement that are distinct from corticospinal projections (Conner et al, 2021; Moreno-Lopez et al, 2021). Further, both corticospinal projections, as well as cortico-brainstem and brainstem-spinal projections show a high degree of plasticity after central nervous system (CNS) damage that contributes to motor recovery (Bachmann et al, 2014; Kaiser et al, 2019), with these distinct projections potentially mediating distinct elements of functional motor recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we chose the corticospinal tract of the spinal cord as an example to characterize and analyze the CNS myelin. The corticospinal tract is a white matter motor pathway that conveys motor commands from the brain to spinal motoneurons ( Moreno-Lopez et al., 2021 ).…”
Section: Expected Outcomesmentioning
confidence: 99%
“…This arrangement allows corticospinal projections to the lumbosacral spinal cord to function as a substrate for the coordinated and automatic control of the lower limbs with incorporation of ongoing afferent input, rather than directly relaying the cortical commands on specific motor pools during each individual movement (e.g., steps). The distinct physiological and functional role of the corticospinal projections in the modulation of the lumbar sensorimotor network was demonstrated in rodents [46]. Specifically, it has been proposed that, at lumbar level, the main role of the corticospinal tract is the modulation of sensory inputs, which is a critical component of the selective regulation of sensory feedback used to ensure well-coordinated movements of the hindlimbs.…”
Section: Modulation Of Spinally Evoked Motor Potentials Prior To the ...mentioning
confidence: 99%